Feasibility of 3D Ultrasound to Evaluate Upper Extremity Nerves - Girtler, M.-T.; Krasinski, A.; Dejaco, C.; Kitzler, H. H.; Cui, L. G.; Sherebrin, S; Gardi, L.; Chhem, R. K.; Fenster, A.; Romagnoli, C.; De Zordo, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: This study investigates the performance of a 3 D Ultrasound (US) system in imaging elbow and wrist nerves. Materials and Methods: Twenty healthy volunteers with asymptomatic median, ulnar and radial nerves were prospectively investigated. Bilateral 3DUS scans of the elbows and wrists were acquired by using a commercially available US scanner (18 MHz, AplioXG, Toshiba) and stored as a 3 D volume by a dedicated software (CURE, Robarts Research Institute). Retrospectively, qualitative (image quality, atypical nerve location, findings potentially associated with compression neuropathy) and quantitative (cross-sectional area measurements) evaluations were performed. Results: In all 200 nerves 3DUS was feasible (100 %). Image quality was insufficient in 13.5 % (25 ulnar nerve elbow, 2 radial nerve) and sonomorphology was not assessable in those nerves. Measurement of cross sectional areas was feasible in all nerves (100 %). Median cross-sectional area (range) were: median nerve elbow 7 mm2 (6 – 9), radial nerve 3 mm2 (1 – 4), ulnar nerve elbow 8 mm2 (5 – 11), median nerve wrist 8 mm2 (5 – 10), and ulnar nerve wrist 4 mm2 (2 – 6). No significant changes in nerve cross-sectional area along each nerve was found. Ulnar nerve subluxation was found in 2 nerves (6.7 %). No anconeus epitrochlearis muscle or osteophytes were found. Conclusion: 3DUS is a feasible method for assessing nerves of the upper extremity and has been shown to provide a good overview of the median, ulnar and radial nerve at the elbow and wrist, but is limited for evaluation of the ulnar nerve in the cubital tunnel. This technique enables reliable measurements at different locations along the nerve.
Keywords: ultrasound; nervous-peripheral; ultrasound 3 D/4 D